Sistem Ekonomi dan Administrasi Islam - Putra Pratama, Rinaldo; Clapita, Zahra Aprilia; Azhari, Devi Syukri (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The Islamic economic and administrative system is a fundamental aspect of governance based on Sharia principles. Islamic economics emphasizes justice, balance, and social welfare through mechanisms such as zakat, waqf, and the prohibition of riba. Meanwhile, Islamic administration focuses on transparent, accountable governance that prioritizes the well-being of society, guided by the values of the Qur'an and Hadith. This study aims to analyze the concepts, principles, and implementation of the Islamic economic and administrative system in the modern context. Using a qualitative approach based on literature studies, the research finds that the Islamic economic and administrative system remains highly relevant in addressing contemporary global challenges, particularly in promoting economic justice and governance effectiveness. Integrating Islamic values into these systems is expected to contribute to a fairer and more sustainable development.